Molecular Analyses in a Rabbit Model of Craniosynostosis: Likely Exclusion of Known Candidate Genes as the Loci of Origin. (July 2019) - Gilbert, James R.; Taylor, Gwen M.; Losee, Joseph E.; Mooney, Mark P.; Cooper, Gregory M.
Objective: Craniosynostosis (CS) involves the premature fusion of one or more cranial sutures. We work with a naturally occurring rabbit model of CS with an undefined etiology. Known causes of coronal CS were evaluated to identify potential associations with CS in the rabbit. Design: Candidate genes were sequenced in control New Zealand White (NZW) rabbits (n = 4) and synostotic NZW rabbits (n = 4). Variants were identified by alignment using Clustal Omega. Outcome Measures: Single nucleotide variants (SNVs) were classified according to phenotypic associations and predicted impact on protein structure. Human correlates were identified in the database of single nucleotide polymorphisms (dbSNP). Results: A total of 21 SNVs were identified in the 10 genes examined. Variant classification and inheritance patterns are inconsistent with causality. Conclusions: The genetic basis for disease in the CS rabbit likely involves novel loci and is not associated with known causes of coronal synostosis.